Pragmatics in our Grammatical Heritage: اللسانيات التداولية - آلاء عبد نعيم إ.د. (lark, 2020)
Regarding the critics toward the Arabic grammar as a figural grammar without content, It aims to prevent errors utterance. So, it was came out in a ready molded criterion, and the learner’s duty is only to read and memorize them. And forgetting that most of the linguistic texts and grammatical witnesses are not clear from the content which has a benefit at the linguistic utilization , and related hardly with semantics and discourse ambiguity, that has many purposes and goals. So, it is not a totally figural.